Canadian spontaneous coronary artery dissection cohort study: in-hospital and 30-day outcomes - Saw, Jacqueline; Starovoytov, Andrew; Humphries, Karin; Sheth, Tej; So, Derek; Minhas, Kunal; Brass, Neil; Lavoie, Andrea; Bishop, Helen; Lavi, Shahar; Pearce, Colin; Renner, Suzanne; et al. (European heart journal, 2019)
Spontaneous coronary artery dissection (SCAD) was underdiagnosed and poorly understood for decades. It is increasingly recognized as an important cause of myocardial infarction (MI) in women. We aimed to assess the natural history of SCAD, which has not been adequately explored. We performed a multicentre, prospective, observational study of patients with non-atherosclerotic SCAD presenting acutely from 22 centres in North America. Institutional ethics approval and patient consents were obtained. We recorded baseline demographics, in-hospital characteristics, precipitating/predisposing conditions, angiographic features (assessed by core laboratory), in-hospital major adverse events (MAE), and 30-day major adverse cardiovascular events (MACE). We prospectively enrolled 750 SCAD patients from June 2014 to June 2018. Mean age was 51.8 ± 10.2 years, 88.5% were women (55.0% postmenopausal), 87.7% were Caucasian, and 33.9% had no cardiac risk factors. Emotional stress was reported in 50.3%, and physical stress in 28.9% (9.8% lifting >50 pounds). Predisposing conditions included fibromuscular dysplasia 31.1% (45.2% had no/incomplete screening), systemic inflammatory diseases 4.7%, peripartum 4.5%, and connective tissue disorders 3.6%. Most were treated conservatively (84.3%), but 14.1% underwent percutaneous coronary intervention and 0.7% coronary artery bypass surgery. In-hospital composite MAE was 8.8%; peripartum SCAD patients had higher in-hospital MAE (20.6% vs. 8.2%, P = 0.023). Overall 30-day MACE was 8.8%. Peripartum SCAD and connective tissue disease were independent predictors of 30-day MACE. Spontaneous coronary artery dissection predominantly affects women and presents with MI. Despite majority of patients being treated conservatively, survival was good. However, significant cardiovascular complications occurred within 30 days. Long-term follow-up and further investigations on management are warranted.